Teacher Strategies for Achieving Goals in Mathematics Learning in Elementary Schools - Intan, Deyana Nuru (Program Magister Teknologi Pendidikan Universitas Jambi, 2017)
This research aims to describe the strategies teachers apply in achieving mathematics learning goals in elementary schools and the things teachers need to pay attention to in determining these learning strategies. The approach used in this research is a qualitative approach with a case study type of research. Research data was obtained through observation and strengthened by interviews conducted with class V A teachers. Data analysis techniques were carried out by data reduction, data presentation and data verification. The results of this research show that the strategy used by teachers in achieving mathematics learning objectives in class V A is starting with planning to carry out the learning process, in planning activities carried out by designing a Learning Implementation Plan that is adapted to the curriculum and syllabus, as well as preparing media that will be used in learning activities. In conclusion, all mathematics learning activities that have been carried out are very oriented towards the activities and characteristics of students, so that the goals of mathematics learning that are targeted can be achieved well.